Assessment of the phytochemical composition and antimicrobial properties of Tapinanthus bangwensis leaves hosted by the branches of Persea americana - Maxwell Mamfe Sakyiamah; Paa Kwesi Gordon; Peter Bolah; Prince Kyei Baffour; Ebenezer Ehun; Olga Quasie; Doris Kumadoh; Mary-Ann Archer; Susana Oteng Mintah; Alfred Ampomah Appiah (BMC, 2023)
Abstract Background Medicinal plants represent a valuable source for new effective and safe antimicrobial drugs making them an alternative therapy. Existing antimicrobial agents are costly and mostly associated with possible side effects. The aim of the present study therefore, was to assess the antimicrobial property and phytochemical composition of hydroethanolic extract of Tapinanthus bangwensis leaves and its fractions. Method T. bangwensis leaves (harvested from its host plant, Persea americana) was extracted by cold maceration with 70% ethanol and further fractionated with different organic solvents using the solvent partitioning method to obtain the crude extract, petroleum ether, chloroform, ethyl acetate and the resulting aqueous fractions. The phytochemical constituents of the extracts were screened and quantified. Also, the TLC of the extracts were analyzed to serve as a fingerprint. Using the agar diffusion and broth dilution methods, the antimicrobial properties of the extracts were assessed. Results The study showed that the hydroethanolic (70%) crude extract of T. bangwensis leaves and its fractions contain phenolic compounds, flavonoids, saponins, phytosterols and reducing sugars. The phytoconstituents were well extracted into the ethyl acetate fraction than the other fractions evidenced in the high levels (p < 0.0001) of saponins (66.47 ± 1.72% w/w), phenolic compounds (77.75 ± 1.06 mg/100 mg GAE) and flavonoids (44.34 ± 0.06 mg/100 mg QE) contents. From the antimicrobial studies, all the microorganisms tested exhibited varying degrees of susceptibility to the extracts with MIC values between 0.78 to 12.5 mg/mL. The crude extract of T. bangwensis leaves, its ethyl acetate and chloroform fractions also exhibited lethal antimicrobial activity with MLC between 6.25 to 50 mg/mL. Conclusion The crude extract of T. bangwensis leaves and its fractions demonstrated antimicrobial properties against Escherichia coli, Staphylococcus aureus, Staphylococcus saprophyticus and Candida albicans, thereby representing a potential source of natural antimicrobial agent. Further study is required to identify and isolate antimicrobial compounds from the plant for the development of the natural bioactive antimicrobial agents.